Before we were innocent - Berman, Ella (Berkley, 2023)
"A summer in Greece for three best friends ends in the unthinkable when only two return home in this new novel from Ella Berman. . . . Ten years ago, after a sun-soaked summer spent in Greece, best friends Bess and Joni were cleared of having any involvement in their friend Evangeline's death. But that didn't stop the media from ripping apart their teenage lives like vultures. While the girls were never convicted, Joni, ever the opportunist, capitalized on her newfound infamy to become a motivational speaker. Bess, on the other hand, resolved to make her life as small and controlled as possible so she wouldn't risk losing everything all over again. And it almost worked. . . . Except now Joni is tangled up in a crime eerily similar to that one fateful night in Greece. And when she asks Bess to come back to LA to support her, Bess has a decision to make. Is it finally time to face up to what happened that night, exposing herself as the young woman she once was and maybe still is? And what happens if she doesn't like what she finds?"--